A Critique of Asouzu’s Notion of Ihe Mkpuchi Anya (the Phenomenon of Concealment) - Akwaji, Agabi Gabriel; Paschal, Aniah Undie (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
This research work is conscious participation in African philosophy, precisely on Asouzu’s notion of Ihe Mkpuchi Anya (The Phenomenon of Concealment). The work attempts to address some of the challenges of human ambivalent situations that are visible in the way we judge, act, will, value, conceive reality, and so forth. In this work, we argued that human beings are conscious beings. Due to this consciousness, their actions are difficult to predict. Actors themselves often act against their interests because of the unfathomable nature of their actions. Often time they cannot predict themselves, what appeared to be good from the onset may turn out to be bad once it is done. We deduced that if actors can sometimes act against their interests and/ or act to promote their most cherished interests, regardless of negative consequences then, there must be something responsible for that. We concluded that human beings act under the influence of ihe mkpuchi anya (the phenomenon of concealment). This phenomenon can impair our vision, becloud our sights, affect the way we reason and cause us to pass wrong judgments on issues confronting us as individuals and/ or as a community. Finally, we recommended that human beings can act rightly by suppressing and avoiding things that are detrimental to him and or to another. It is only when a man does the above-recommended things that society can grow harmoniously in every aspect. We employed the critical, analytical, expository, and complementary methods in the course of researching.